ANALISIS RISIKO BENCANA KAMPUNG MBAH MARIDJAN TERHADAP BAHAYA AWAN PANAS GUNUNGAPI MERAPI BERBASIS 3D ANALYSIS - Yasin Yusup, (Pendidikan Geografi, 2011)
ABSTRACT Eruption of Merapi Volcano at 2006 aiming to South Slope passing Gendol River generate the damage impact of Kaliadem recreation  and " almost" touch the Kampong of mbah Maridjan. Morphological setting in those zones still able to limit the distribution of Glowing Cloud, so the impact limited. The burying of bunker kill 2 people caused by bunker location which not yet considered the possibility of hot cloud slide away from the channel of K. Gendol. Kampong of mbah Maridjan located in among 2 rivers that is K. Gendol and K. Kuning and encircled by the hills. This hills existence protects the Kampong of mbah Maridjan from the 2006 glowing  cloud slide down by magnitude 2 (Volcanic Explosion Index / VEI). Hill trusted by a local society as protection morphology. Though is safe from the hot cloud, but if the bigger eruption is happened (VEI > 2), risk of mbah Maridjan Kampong to the glowing cloud increase and the possibility of hot cloud slide away from the Cemara hills and run against the Kampong Maridjan become rise. Geographic Information Systems (GIS) by 3D Analysis tools from Arc View; terrain and Image overlay tools from Google Earth used in this research to analyze the relation of Merapi South Slope morphology with the glowing cloud distribution. Transect or profile tools used to know the effectiveness of valley and hill in limiting distribution of the glowing cloud. Here GIS can be told to ease the hazard, vulnerability, and disaster risk of mbah Maridjan Kampong to glowing cloud analysis.